Bias temperature instability analysis on memory properties improved by hydrogen annealing treatment in Ti/HfOx /Pt capacitors. Issue 7 (13th June 2013) - Kim, Hee‐Dong; Yun, Min Ju; Hong, Seok Man; An, Ho‐Myoung; Kim, Tae Geun
Abstract The influence of the hydrogen annealing treatment on the reliability of Ti/HfOx /Pt capacitors is investigated by analyzing bias temperature instability (BTI). As compared to the N2‐annealed sample, in the case of hydrogen‐annealed samples, both the set/reset voltages and currents are reduced from 6.5 V/–1.6 V to 3.8 V/–1.2 V and from 4 mA/170 nA to 800 µA/30 nA at 0.1 V, respectively. Of particular interest is the dramatic reduction in the set voltage variation from 3.3 V to 1.8 V. In addition, in BTI experiments, the current shift at the high resistance state (HRS) is reduced from 1.5 µA to 40 nA under a bias stress of –1 V/1000 s and from 40 µA to 0.5 µA under a temperature stress of 120 °C/1000 s. These results show that the hydrogen annealing treatment is very effective in improving the reliability of RRAM cells because it reduces the leakage current under bias temperature stress. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)